ASNAT: Nabi Surgawi Yang Tersembunyi - Asnath Niwa Natar (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2017)
Abstract: There are some salient female figures who play significant roles in the Bibles stories. Unfortunately, their stories are not described sufficiently; or in other words, males roles have dominated mostly and disguised them. Female figures are conveyed in relation to the men, such as wives, mothers and daughters. Patriarchal culture has abolished womens roles in history, cultures and religions which give crucial impacts to the exclusion of women in most of their lifes aspects. One of such women whos deprived is Aseneth, the Josephs wife, the Potipherahs daughter. Aseneth is the significant female figure who plays an outstanding role. Furthermore, shes an heavenly prophet, to whom the mystery of Gods revealed unspeakably. Its related to the event when God touched Aseneths mouth with the honeycomb, the similar significant story of the calling of the prophets, as it happened upon Jeremiah (Jer 1:9) and Isaiah (Isa 6:6ff). Aseneths figure will be able to inspire and strengthen women to come out from their silence and reluctance. Otherwise, she will have encouraged women to struggle against the obstacles of cultures and religion faced for the sake of mens and womens equal life. Keywords: Woman, Patriarchal, Aseneth, Joseph, prophet, Culture, religion, equal. Abstrak: Ada banyak tokoh-tokoh perempuan yang cukup berperan dalam Alkitab, namun kisah mereka dipotong atau dihilangkan demi menonjolkan peran dan dominasi laki-laki. Kaum perempuan hanya disebut sepintas lalu dalam kaitan dengan laki-laki, yaitu sebagai istri, ibu dan anak perempuan. Budaya patriarkhi telah menyingkirkan perempuan dalam sejarah, budaya dan agama yang berdampak pada penyingkiran kaum perempuan hampir dalam semua bidang kehidupan termasuk dalam kehidupan keagamaan. Salah satu kisah perempuan yang dihilangkan atau disembunyikan adalah kisah Asnat, anak Fotifera dan istri Yusuf. Asnat adalah seorang perempuan yang aktif bahkan seorang nabi Surgawi, dimana kepadanya disingkapkan rahasia Allah yang tak terkatakan. Hal ini dihubungkan dengan peristiwa disentuhnya mulut Asnat dengan sarang lebah, sebagai sebuah kisah pemanggilan nabi-nabi. Peristiwa yang sama terjadi pada pemanggilan Yeremia (Yer 1:9) dan Yesaya (Yes 6:6 dst) sebagai nabi. Kisah Asnat akan memberikan inspirasi dan kekuatan bagi kaum perempuan untuk keluar dari kebungkaman dan kepasifan mereka serta berjuang melawan rintangan-rintangan budaya dan agama yang ada demi kehidupan yang setara antara laki-laki dan perempuan. Kata-kata Kunci: Perempuan, Patriarki, Asnat, Yusuf, nabi, budaya, agama, kesetaraan.